The Allergenicity Potential of Edible Freshwater Fish - Atika Hanum Falihah; Muhammad Novrizal Abdi Sahid; Ika Puspitasari (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
A Freshwater fish is a popular type of fish consumed in Indonesia besides seawater fish. However, until now the most available information regarding the potential allergenicity of fish is only related to seawater fish. The potential allergenicity of freshwater fish has not been studied much, so it has not been identified and characterized. Based on this, this review aims to collect information regarding the potential allergenicity of protein in freshwater fish and the effect of processing on this potential. The potential allergenicity of proteins in several freshwater fish has been confirmed by immunoblotting and ELISA, namely mujair, nile, catfish, mas, toman, janjan, tambakan, tiger scat, barramundi, and eel. The identified allergenic proteins include parvalbumin, tropomyosin, enolase, aldolase, creatine kinase, triosephosphate isomerase, pyruvate kinase, lactate dehydrogenase, glucose-6-phosphate isomerase, and glyceraldehyde-3-phosphate dehydrogenase. In addition, several proteins in other freshwater fish also have allergenicity potential but have not been confirmed through research, namely pomfret, gourami, snakehead, catfish, eel, betutu, and cetol. The potential allergenicity of fish protein is also influenced by the processing process. Changes in the potential allergenicity are related to the characteristics of each allergen protein. Therefore, it is necessary to select the appropriate processing so that potential allergenicity can be suppressed.